Creative identity (re)Construction, creative community building, and creative resistance: A qualitative analysis of queer ingroup members' tweets after the Orlando Shooting. (December 2019) - Jenkins, Elizabeth M.; Zaher, Zulfia; Tikkanen, Stephanie A.; Ford, Jessica L.
Abstract: With the proliferation of social media, a growing body of literature explores the significance of virtual grief, social support, and social capital in the construction of identity and community online. However, there is a dearth of research on how queer members use social media, particularly Twitter, as a tool to claim and re-define their identity—especially when their identity is under threat. The goal of this study is to understand how members of the queer community linguistically responded to the threat to their identity and safety that was caused by the shooting that took place on June 12, 2016, at the Pulse Nightclub in Orlando, Florida. To achieve this goal, we use Social Identity Theory (SIT) as a framework to examine how queer individuals use a creative language strategy to redefine their shared identity when it is threatened. This study used a qualitative iterative analysis of tweets posted by queer individuals to determine how this group identified as ingroup after the Orlando shooting. The study reveals that members of the queer community communicatively responded to the Pulse shooting through social creativity. Specifically, members of the queer community responded to threats through using creative language that fostered stronger ingroup collaborative identities by provoking a) creative identity (re)construction, b) creative community building and c) creative resistance. This study advances SIT by providing additional evidence that the strategy of using creative language by a minority ingroup has the ability to support simultaneously salient and threatened identity. Highlights: Creative identity (re)construction. Creative community building. Creative resistance.